Youth Mental Health In Light Of The Story Of Ashab Al-Kahfi: A Thematic And Analytical Study Of Surah Al-Kahf, Verse 13: الصحة النفسية عند الشباب من خلال قصة أصحاب الكهف (دراسة موضوعية وتحليلية للآية 13 من سورة الكهف) - Muhtadin, Ali; Aulia, Dea (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) ZAD, 2025)
The rapid development of technology has made social issues increasingly complex. Mental disorder, commonly referred to as